2008
DOI: 10.1002/app.27941
|View full text |Cite
|
Sign up to set email alerts
|

Change in fiber properties due to the heat treatment of nylon 6 tire cords

Abstract: Nylon 6 is used as a reinforcing material in different rubber products. However, as it is a thermoplastic material, it may undergo some kind of thermal shrinkage during the vulcanization of rubber, which leads to dimensional stability problems in the rubber product. To prevent this, we subjected nylon 6 to some kind of thermal treatment at higher temperatures. During thermal treatment, there was some change in the mechanical properties, shrinkage which may have been correlated with changes in the crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The variation of shrinkage force against exposure time in isothermal condition at different temperatures of heat treatment is presented in Figure 1. It was also observed from this figure that at all temperatures of thermal treatment initially the shrinkage force increases with exposure time almost linearly and then attains a plateau value within 30–50 s similar to nylon 6, as observed in our earlier studies 26. However at very high temperature (≥170°C) of exposure, small drop in shrinkage force beyond 30–50 s is not observed in case of polyester as that of nylon 6.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The variation of shrinkage force against exposure time in isothermal condition at different temperatures of heat treatment is presented in Figure 1. It was also observed from this figure that at all temperatures of thermal treatment initially the shrinkage force increases with exposure time almost linearly and then attains a plateau value within 30–50 s similar to nylon 6, as observed in our earlier studies 26. However at very high temperature (≥170°C) of exposure, small drop in shrinkage force beyond 30–50 s is not observed in case of polyester as that of nylon 6.…”
Section: Resultssupporting
confidence: 86%
“…The drop in tenacity over the whole temperature range (150–210°C) of heat treatment is gradual. However, in our earlier work, we observed that there was a drastic drop in tenacity as well as elongation at break for nylon 6 tire cord at 210°C 26. This may be due to the difference in the melting point of both the fibers.…”
Section: Resultsmentioning
confidence: 66%
“…It causes shrinkage of up to 3% in the hybrid cord. This means some shrinkage will remain in the samples under a load of 1800 gf 20,21 . But under 600 gf, the specimens have been allowed to shrink in the first heating step, and reheating causes little residual shrinkage.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of DSC-crystallinity is calculated from the melting enthalpy values employing equation (1) where χ c is the degree of DSC-crystallinity, ΔH m is the melting enthalpy of the sample under consideration and ΔHm o is the melting enthalpy of the 100% crystalline sample. A typical value of 191 J/g was taken for the 100% crystalline PA6 [38].…”
Section: Methodsmentioning
confidence: 99%